NAO as a Copresenter in a Robotics Workshop - Participant’s Feedback on the Engagement Level Achieved with a Robot in the Classroom - Hernández Cedeño, Joseiby (2018)
Robotics, combined with computer science and human-centered studies, can have a substantial impact in areas such as education and innovation. Robots have proven to be a good tool to gain and maintain users’ involvement in different activities. In education, robots can be used as teaching assistants to improve participation, enhance concentration or just to get students’ attention. In this research, we involved an NAO, a humanoid robot, in a workshop presentation with the aim of measuring the impact of this technique on the level of engagement showed by the participants. The robot was programmed to simulate speech and gesticulate while it talked to apply the Wizard of Oz technique.